2016
DOI: 10.1097/jpn.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Just-in-Time Video Laryngoscopy Versus Direct Laryngoscopy for Neonatal Intubation

Abstract: As neonatal endotracheal intubation (ETI) is a low-frequency, high-consequence event, it is essential that providers have access to resources to aid in ETI. We sought to determine the impact of video laryngoscopy (VL) with just-in-time training on intubation outcomes over direct laryngoscopy (DL) when performed by neonatal nurses. We conducted a prospective, randomized, crossover study with neonatal nurses employed at a level 2 neonatal intensive care unit (NICU). Nurses performed both DL and VL on a neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It was seen that the use of videolaryngoscopy yielded a faster time to tracheal intubation than fiberoptic bronchoscopy [13, 14]. In another study by Grgurich et al, there was no significant difference in time to tracheal intubation and first attempt success between videolaryngoscopy and awake fiberoptic intubation [15]. Other papers have alluded to the use of a combination of the above-mentioned methods, usually after failure to intubate by conventional means.…”
Section: Discussionmentioning
confidence: 99%
“…It was seen that the use of videolaryngoscopy yielded a faster time to tracheal intubation than fiberoptic bronchoscopy [13, 14]. In another study by Grgurich et al, there was no significant difference in time to tracheal intubation and first attempt success between videolaryngoscopy and awake fiberoptic intubation [15]. Other papers have alluded to the use of a combination of the above-mentioned methods, usually after failure to intubate by conventional means.…”
Section: Discussionmentioning
confidence: 99%
“…VL improved the view of the glottis in both uncomplicated and difficult intubation situations, increased the success rate in the first attempt at intubation, and reduced the rate of complications, such as damage to oral structures, bradycardias and brief hypoxia (7)(8)(9)(10)(11)(12). Furthermore, several studies in children have confirmed the advantages of VL in difficult intubation conditions and the possibility to reduce TIAEs (tracheal intubation associated events) (13)(14)(15). In particular, VL has shown that it is a suitable and helpful tool for teaching inexperienced medical professionals (13,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Just-in-time training (JITT), which originated in the automotive industry, is a planned, on-the-job, short unit of instruction provided on-demand in close proximity to the need for the training [7]. JITT has demonstrated increased learner confidence in lumbar puncture, improved skill in VL and pediatric advanced life support, and decreased procedural skill decay in transvenous pacing catheter placement [8][9][10][11]. Its advantages include short time for training, in-situ location for training, and availability for repeated training.…”
Section: Introductionmentioning
confidence: 99%